System-oriented (collective) career versus self-oriented career - Bieńkowska, Jolanta (Contemporary trends in business security: Problems and challenges of eastern economies, 2022)
Nowadays, it is almost an axiom that career development is determined by satisfying the need for self-fulfilment. However, this need is not biological but social and cultural. Thus, the determinants of choosing a career type result (among others) from the relationship between an individual and a social group, hence we can distinguish extreme models of career – collective-oriented versus individual-oriented. The career types proposed in this study were characterized using Parsons’ base variables, which were applied to describe the differences between the collective and liberal systems and between the two types of career mentioned above. The article aims to present arguments to illustrate how the need and the ability to free oneself from social anxiety through gaining recognition determines professional behaviour. The starting point for its formulation was the assumption that a commonly felt social anxiety causes a need to gain recognition of the collective. The individual’s need to free themselves from social anxiety and the ability to do so leads to a self-centred career model that is increasingly common in the age of information civilization. The article analyzes the socio-cultural factors determining collectivist and individualistic orientation and their psychological and social consequences